“LA CLASE INVERTIDA EN EL APRENDIZAJE DE RAZONES TRIGONOMÉTRICAS EN LOS ESTUDIANTES DE DÉCIMO AÑO DE EDUCACIÓN BÁSICA DEL COLEGIO MIGUEL ÁNGEL LEÓN PONTÓN EN EL PERÍODO ABRIL – AGOSTO 2019” - Quituisaca Guamán, Cristian Wilian (2019)
At present, the application of new strategies is consistent with the advancement of the sciences and contemporary technologies, being fundamental processes for student motivation, improve the process of teaching and learning in mathematics. Creating a pleasant atmosphere in the classroom, that is why it was necessary to carry out the present investigative work, whose purpose is to analyze the contribution of the class inverted in the learning of trigonometric ratios in the students of the tenth year of Basic General Education of the Miguel Ángel León Pontón the period April - August 2019, This research consists of 5 chapters: referential framework, theoretical framework, methodological framework, analysis and interpretation of results, conclusions and recommendations; the population object of study is of 331 learners was chosen, a random sample – a boost of 30 students of the parallel H, This study has a non-experimental design by not manipulating the variables, applied the class upside down with the help of videos, teamwork, promoting independent learning. In the resolution of exercises of trigonometric ratios; to process the data, it was used the software package Microsoft Office Excel software by using descriptive statistical techniques. Therefore it appears that the inverted class helps the student to improve their investigative qualities, and is learning process, taking a favorable acceptance of the students to this methodology which it is suggested to apply it of correctly and excessive use.